Inhaled aerosolized nicotine suppresses the lung eosinophilic response to house dust mite allergen - Gahring, Lorise C.; Myers, Elizabeth J.; Rogers, Scott W. (American journal of physiology. Lung cellular and molecular physiology, 2020)
Nicotine of unprecedented concentrations and purity is being inhaled by those using commercially available electronic nicotine delivery systems (ENDS). The consequences of this route of self-administration on the immunological response to inhaled allergens are not known. In mice, sensitization and inhalation challenge with the common environmental house dust mite (HDM) allergen is an experimental model of this response. When mice were exposed to aerosolized nicotine base (aeroNic) twice daily, 5 days/wk for 8 wk, the HDM-induced recruitment of eosinophils (EOS) was substantially reduced as measured in bronchial alveolar lavage fluid (BALF). Oral nicotine administration had no effect. HDM challenge in the presence of nicotinic receptor subtype α7 (α7)-specific type-1 positive allosteric modulators (PAMs) was alone sufficient to suppress EOS. RNA analysis of alveolar macrophages (AM) collected from BALF after HDM challenge of aeroNic revealed that α7 activation strongly suppresses initiation of Ccl24 (eotaxin 2) transcription. To examine possible cellular signaling mechanisms coupling α7 to Ccl24 transcription, an AM culture model system was used. In AM cultures of freshly collected BALF, Ccl24 transcription was robustly activated by a mixture of IL-4 and IL-10, and this was suppressed by coapplication of type-1 PAMs through a pathway that requires p38MAPK but is independent of Jak2. These results suggest that the EOS response to HDM inhaled allergen is subject to modulation through activation of the α7 receptor and suggest that the allergic response may be substantially modified in ENDS users.